UPAYA MEMBRANDING DESTINASI PARIWISATA KOTA SERANG - Sahabudin, Arfah; Tahir, Rusdin; Saleh, Nursahdi (Jurnal Master Pariwisata (JUMPA); Volume 09, Nomor 02, Januari 2023, 2023)
One of the efforts to increase the attractiveness of tourism destinations is through tourism destination branding. Efforts need to be made to realize tourism destination branding. This study aims to describe efforts to compare tourism in Serang Municipality based on its tourism potential. The research method is a descriptive research method with a qualitative approach. Primary data is obtained by conducting interviews and direct observation of informants who are considered to understand tourism conditions. Secondary data was obtained through journals, tourism reports and related literature studies. Then it was analyzed using an interactive model through data reduction, data presentation and then drawing conclusions from the analysis. It was found that the Serang Municipality Youth and Sports Tourism Office had made various efforts to increase the attractiveness of tourism destinations by carrying out several stages to build tourism destinations through Group Discussion Forums, logo and tagline design competitions, procurement and naming of tour buses, making promotional videos, and utilizing Instagram social media. The next step is to develop a tourism destination brand preferably through destination governance and sustainable tourism marketing and digital transformation. Keywords: tourism destination branding; digital branding; heritage tourism; urban tourism